Reliability-driven assessment of GaN HEMTs and Si IGBTs in 3L-ANPC PV inverters - Gurpinar, Emre; Yang, Yongheng; Iannuzzo, Francesco; Castellazzi, Alberto; Blaabjerg, Frede (IEEE, 2016)
In this paper, thermal loading of the state-of-the-art GaN HEMTs and traditional Si IGBTs in 3L-ANPC PV inverters is presented considering real-field long-term mission profiles (i.e., ambient temperature and solar irradiance). A comparison of Si IGBT against GaN HEMT with three different possibilities: 1) with TIM at 10 kHz, 2) without TIM at 10 kHz, and 3) with TIM at 300 kHz has been performed. The assessment results indicate lower thermal stress with GaN HEMT devices at 10 kHz in comparison to Si IGBT. At high switching frequencies, the results show significant system level cost savings can be achieved without compromise of operating efficiency with GaN HEMTs. Both simulations and experimental tests are provided to demonstrate the thermal loading analysis approach. More important, the proposed analysis and comparison approach can be used for lifetime and reliability analysis of wide-bandgap devices.